Assessment of three new parasite lactate dehydrogenase (pan-pLDH) tests for diagnosis of uncomplicated malaria - Fogga, Carole; Twesigye, Rogers; Batwala, Vincent; Piola, Patrice; Nabasumba, Carolyn; Kiguli, James; Mutebi, Frederick; Hook, Christa; Guillerm, Martine; Moody, Anthony; Guthmann, Jean-Paul (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2008)
A study to assess the diagnostic capabilities of three parasite lactate dehydrogenase (pan-pLDH) tests, Vistapan®, CarestartTM and Parabank®, was conducted in Uganda. An HRP2 test, Paracheck-Pf®, and a Giemsa-stained blood film were performed with the pLDH tests for outpatients with suspected malaria. In total, 460 subjects were recruited: 248 with positive blood films and 212 with negative blood films. Plasmodium falciparum was present in 95% of infections. Sensitivity above 90% was shown by two pLDH tests, Carestart (95.6%) and Vistapan (91.9%), and specificity above 90% by Parabank (94.3%) and Carestart (91.5%). Sensitivity decreased with low parasitaemia (_2 trend, P < 0.001); however, all tests achieved sensitivity >90% with parasitaemia ≥100/_l. All tests had good inter-reader reliability (_ > 0.95). Two weeks after diagnosis, 4—10% of pLDH tests were still positive compared with 69.7% of the HRP2 tests. All tests had similar ease of use. In conclusion, two pLDH tests performed well in diagnosing P. falciparum malaria, and all pLDH tests became negative after treatment more quickly than the HRP2. Therefore the rapid test of choice for use with artemisinin-combination therapies in this area would be one of these new pLDH tests.
Keywords: Malaria; Diagnosis; Rapid diagnostic tests; Validity; Sensitivity and specificity; Parasite lactate dehydrogenase tests